The Effect Of Toddler Mothers’ Classes On Mothers’ Attitudes In Providing Complementary Feeding (Mpasi) To Infants Aged 5–6 Months In The Working Area Of Rongga Health Center In 2025 - Fathia Rizki; Meita Dhamayanti; Aulia Raisya Azzahra (CV. AFDIFAL MAJU BERKAH, 2026)
Stunting remains a public health problem in Indonesia, including in the working area of Rongga Community Health Center. One of the contributing factors to stunting is the inappropriate provision of complementary feeding (MP-ASI). The “Mother and Toddler Class” is an educational program designed to improve mothers’ attitudes toward MP-ASI provision. This study aimed to determine the effect of the Mother and Toddler Class on mothers’ attitudes in providing MP-ASI to infants aged 5–6 months in the Rongga Community Health Center working area in 2025. This research used a pre-experimental design with a one-group pretest-posttest approach. The study sample consisted of mothers with infants aged 5–6 months, selected using stratified random sampling with a lottery method. Data were collected through attitude questionnaires administered before and after the intervention. Data analysis was performed using the McNemar test. The results showed that the average attitude score of mothers increased after participating in the Mother and Toddler Class. Statistical analysis indicated a p-value < 0.05, meaning there was a significant difference between mothers’ attitudes before and after attending the class. The Mother and Toddler Class had a significant effect on improving mothers’ attitudes in providing MP-ASI to infants aged 5–6 months. This program should be conducted routinely to support stunting prevention through improved complementary feeding practices.